CORPORATE GOVERNANCE AND CORPORATE RISK DISCLOSURE EVIDENCE FROM MALAYSIA - Kurniawanto, Hudi (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The main objective of this study is to analyse the impact of corporate governace on the corporate risk disclosure of Malaysian corporations. The research has used quantitative methods, namely, regression testing, in the form of descriptive statistics and multiple regression analysis. The data obtained in this research are analyzed by using the Statistical Product and Service Solutions (SPSS). To answer the study objectives, the researcher analyzes the nonfinancial companies listed on Bursa Malaysia. The results of this study indicate that board size affects corporate risk disclosure, while board independence no affects corporate risk disclosure. It shows that the greater the board size, the better the level of supervision and pressure on management, thus encouraging management to be more transparent corporate risk disclosure. This study can contribute to the government as a reference in the preparation of corporate risk disclosure policies to increase investor confidence in company risk disclosure information produced by public companies. Keywords: Corporate Risk Disclosure, Corporate Governance, Board Size, Board of Independence, Malaysia.